IMPLEMENTASI KOMPRESI CITRA DIGITAL DENGAN MENGATUR KUALITAS CITRA DIGITAL - Bayu Dwi Raharja; Paulus Harsadi (STMIK Sinar Nusantara, 2018)
Image is one of the most popular media used in today’s information exchange. Increased needs for the use of images must also be supported by available storage media. The imagery generated from each high-resolution camera device has a relatively large size. Image compression is a data compression application performed on digital image in order to reduce the redundancy of the data contained in the image so that it can be stored or transmitted efficiently.Image compression techniques can be grouped into two namely lossless compression and lossy compression. Lossy compression is a method to compress the image where compressed image decompression results are not the same as the original image because there is missing information, but still can be tolerated by the eye. Lossless compression is an image compression where the decompression of compressed images is the same as the original image, no information is lost. For the following image compression by reducing image quality that can still be tolerated by the eye.